Implementation of a finger force detection platform with a graphical user interface - Romero E. (2017)
This paper presents the implementation of a Finger force detection platform capable to measure the exerted forces by the index, middle, ring and little finger in single-axis direction (flexion); and in dual-axis direction (flexion/adduction) by the thumb. It can be adapted to different sizes in both right or left hand. A test protocol is established. Also, a Graphical User Interface (GUI) is developed in order to assist the subject during the test. The results show the maximum forces developed by each finger among Peruvian participants.